(3Ndb GdEfSGf heeG Ndb heG QcH ajgs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd Mfjf Hf ESMGb GdeJWHH(B: (3bGd YHOGdefYe Hf EOQjS (B: (3MOKfG hgH EHf efHg Cfg hLO ai GdJhQGI UaI BOe Mjf Ndbg Gddg YR hLd hGHJOGg s
(3BNQgG (B:s
(3BNQg hbaI cGJH, hjfJgi GdehLhO efg Hbhdg (B: (3hGYde Gf GdHdZe jcKQ ai KdGKI CTgQ(B: (3OLfHQ hjfGjQ s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B86 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs